Selective dissolution of vanadium(V) from spent petroleum catalysts by oxalic acid solution - Le M.N.; Lee M.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The spent petroleum catalyst contains a significant amount of vanadium and its recovery is essential. Oxalic acid has good metal selectivity due to its complex properties. Leaching experiments with oxalic acid were done to investigate the dissolution behavior of vanadium from spent petroleum catalyst by varying leaching conditions, such as temperature, concentration, pulp density, stirring speed and time. Vanadium and molybdenum were selectively dissolved by oxalic acid from the spent catalysts, while the leaching percentage of other metals was very low. However, the leaching percentage of vanadium by oxalic acid was lower than 45% in most of the leaching conditions. Our results provide some basic information on the dissolution of valuable metals from the spent catalyst by using organic acid.